Highly efficient green InP-based quantum dot light-emitting diodes regulated by inner alloyed shell component - Peng Yu; Sheng Cao; Yuliang Shan; Yuhe Bi; Yaqi Hu; Ruosheng Zeng; Bingsuo Zou; Yunjun Wang; Jialong Zhao (Light: Science & Applications, 2022)
In this work, the pure green-emitting InP/ZnSexS1−x/ZnS quantum dots and their light-emitting diodes with high efficiency were successfully obtained by regulating the components of inner alloyed shell ZnSexS1−x layer.